PENGARUH TERPAAN MEDIA TERHADAP SIKAP KAUM IBU DALAM PENDIDIKAN ANAK - Widyaningrum, Retno (Universitas Prof. Dr. Moestopo (Beragama), 2013)
In the current era of globalization, the mass media is a means to obtain the information and entertainment that hasbecome a necessity that can not be separated again in everyday life. Current information and entertainment hasbecome a commodity that can generate money for the managers of mass media. In line with the growth of communicationtechnology, mass media has grown to be an industry that is vital for a country. One important characteristicof the current era of globalization is the rapid development of communication, such as the emergence ofa satellite dish, cable TV, internet, teleconferencing, etc., which results in loss of borders of a country due to thereach of the mass media are almost limitless.